Elastomer coils for wearable MR detection. Issue 5 (12th January 2021) - Port, Andreas; Luechinger, Roger; Brunner, David O.; Pruessmann, Klaas P.
Abstract : Purpose: To explore the use of conductive elastomer for MR signal detection and the utility of this approach for wearable detector arrays. Methods: An elastomer filled with silver microparticles was used to form stretchable radiofrequency coils for MR detection. Their electrical performance in terms of the Qunloaded and Q ratio was assessed in the relaxed state and under repeated strain up to 40%. In a phantom imaging study, the signal‐to‐noise ratio yield of conductive elastomer coils was compared with that of a reference copper coil. Four elastomer coils were integrated with a stretchable textile substrate to form a wearable array for knee imaging. The array was employed for multiple‐angle and kinematic knee imaging in vivo. Results: The elastomer coils proved highly stretchable and mechanically robust. Upon repeated stretching by 20%, a medium‐sized coil element settled at Qunloaded of 42 in the relaxed state and 32 at full strain, reflecting sample‐noise dominance. The signal‐to‐noise ratio of elastomer coils was found to be 8% to 16% lower than that achieved with a conventional copper coil. Multiple‐angle and kinematic knee imaging with the wearable array yielded high‐quality results indicating robustness of detection performance against stretching and warping of the array. Conclusion: Conductive elastomer is a viable material for MR detection. Coils made from this material reconcile high stretchability and adequate electrical performance with ease of manufacturing. Conductive elastomer also offers inherent restoring forces and is readily washable and sanitizable, making it an excellent basis of wearable detector front ends. Abstract : Click here for author‐reader discussions